Pollinators in a changing world: climate change and grazing impacts on bee communities - Brunette, August James (My University, 2025)
Pollinators face many threats today including habitat loss and fragmentation, increased pesticide usage, and new pathogens. Climate change can accentuate these threats through increased temperatures, expanded arid areas, and more frequent and intense extreme weather events. Additionally, grasslands are among the world’s most imperiled ecosystems, and bees in the prairies of Kansas face a variety of challenges. Kansas prairies vary based on their management from cattle grazing as well as along a longitudinal precipitation gradient. The objectives of this work are to 1) understand the effects of climate change on pollinators and identify knowledge gaps in this field and 2) determine the effects of grazing on prairie bee communities along a precipitation gradient in Kansas. To better understand how climate change impacts pollinators we conducted a systematic review of the literature and utilized a vote-counting approach to summarize the results. We found that climate change has an overall negative impact on pollinators which includes effects like, range reductions, phenological mismatch, and reduced pollinator health and fitness. Community level effects such as abundance, richness, and diversity showed mixed responses indicating that pollinator species respond differently to climate change. To identify the effects of grazing on prairie bee communities throughout Kansas, we sampled 30 prairie sites spread across the precipitation gradient found in the state during the summer of 2023. These sites were divided evenly amongst tallgrass, shortgrass, and mixedgrass prairies. Within each prairie type, five sites were grazed and five were ungrazed. We found that bees were most impacted by grazing in the shortgrass prairies of western Kansas where grazing had the greatest effect on bee abundance and community composition. We also found that region effects usually had a stronger effect on bee communities than grazing, and that these effects were often mediated through differences in floral abundance. These findings offer insights into how a changing climate, and management practices can impact pollinators, while informing bee conservation efforts in Kansas and identifying knowledge gaps and directing future research to protect pollinators globally.
Keywords: Pollinator; Climate change; Grazing; Bees